Sociology in literature - سیّد علی‌محمّد سجّادی (تاریخ ادبیات)
The 7th century of Hijri is a completely exceptional time in all aspects of Iran and Iranian life. The devastating Mongol campaign and its ominous effects revealed the imprudence of the monarchy and forced the helpless people to react differently to the worst global event ever. This action and reaction brought great social phenomena, some of which can be seen in the literary and historical texts of that time. The main topic of this research is to search and analyze the effect of those phenomena on the manifestations of Iranian life, because the recognition of the Iranian identity and the explanation of its components will make the new generation look at its past clearly in the mirror of time and learn from it. The contents that have been examined under six general headings in this research are parts of social phenomena that must be addressed and their aspects recognized.